Metadiscourse and Rethorical Moves in English Abstract Section of Undergraduate Students' Final Project at Universitas PGRI Ronggolawe, Tuban - Hadi, Dholiful; Warsono, Warsono; Faridi, Abdurrahman (English Education Journal, 2020)
The aims of the research are to analyze how metadiscourse types is used to accompany the moves in English abstract section of undergraduate students' final project, to explain how rhetorical moves are used in English abstract section of undergraduate students' final project, and to enlighten how metadiscourse functions are applied in relation to the rhetorical moves in the abstract section of undergraduate students' final project at Universitas PGRI Ronggolawe, Tuban. The research was descriptive qualitative research in order to answer the research problem definitely. The research identifies the meaning reflected and particular characteristic in the use of rhetorical moves and metadiscourse. The result shows that the use of interactive metadiscourse tends to be dominant in students' final project abstracts. Almost all of students write the methods of rhetorical moves in their abstract. The move gives a good indication of the information on data, procedures and methods used. The further researchers on teaching writing the final project abstract are suggested to conduct both metadiscourse and rhetorical moves aspect so the students will become more capable of determining the particular kinds of metadiscourse which should be applied in each move of writing abstract.